Estudo multivariado de algumas propriedades termodinâmicas dos elementos terras raras - Pereira, Hercules Abie (2019)
Lanthanides (La-Lu), Yttrium and Scandium form the group of rare earth elements (REE) are classified as light (LREE) and heavy (HREE). These elements are gaining prominence in surveys due to their economic potential as well as their industrial applications. The REEs have the effect of lanthanide contraction, which keeps their values of ionic radius and ΔfH° close, which causes the REEs to substitute essential ions such as Fe2+, Fe3+ and Ca2+ in plant matrices. A multivariate statistical study was carried out in order to verify if there is a grouping of the REE according to their extensive properties of ΔfH°, ΔfSo, ΔfGo and So. The main components analysis showed the effect of the counterion on ΔfH°, where the OH-, Cl-, PO43- variables showed a decreasing force effect in this thermodynamic parameter in the OH-> PO43-> Cl- order, and indicated that the number of atoms of ligand oxygen induces the value of ΔfH°. The hierarchical cluster analysis performed with the values of ΔfH°, ΔfSo, ΔfGo and So divided the compounds of (REE)FeO3, (REE)PO4, (REE)2O3, (REE)O2, (REE)2O2CO3II, (REE)2Zr2O7 and REE(OH)3 according to their molecular characteristics. Considering the values of ΔfH°, they were divided into three groups H (La, Ce, Pr, Nd and Sm), G (Eu) and F (Gd, Tb, Dy, Tm, Ho, Y, Er, Yb, Lu). The subdivision carried out with values of ΔfH° corroborates with the literature that classifies the REEs in LREE and HREE and assists in the understanding of the greater stability of the REE compounds found in geological matrices.